Ex vivo Resection for Renal Cancer: Indications and Results in Specific Clinical Scenarios - Danilo Coco; Silvana Leanza (Journal of Renal and Hepatic Disorders, 2021)
Purpose: To retrospectively evaluated databases for indications and results of “bench surgery Technique” in ex vivo or ex situ renal cancer resection as a lost alternative of savage renal function in renal malignancy.